Platform Business Models: Network Effects and Value Creation Logic - Natalya N. MASYUK; Marina A. BUSHUEVA; Alexey E. KIRYANOV; Fuxue ZHENG (Communications of International Proceedings, 2022)
One of the phenomena of the coming digital revolution is digital platforms embedded in companies' activities and completely changing the entire business. The paper shows that platform business models are more efficient than traditional business methods. It has been convincingly argued that platform solutions are an inevitable consequence of digital transformations while emphasizing that network effects and technological and digital innovations are key factors in developing platforms, which contribute to creating new networks and alliances. Particular attention is paid to the problem and the logic of creating value/value. As illustrations, statistical data on the capitalization of the world's largest companies in 2021 using platform business models - Apple, Microsoft, Alphabet, Amazon, Tesla, and Facebook are given.
Keywords: Digital Platforms; Platform Business Model; Network Effects; Value